Mental Health Consequences of COVID‐19 Vaccine Side Effects: Findings From a Cross‐Sectional Analysis - Md. Shajadul Islam; Md. Bony Amin; Md. Hafizur Rahman; Fardana Binte Zaman; Sajib Rangder; Faiaz Morshed Khan Jilan; Wajihantun Nesa Chowdhury; Sanjarah Tamim; Nusrat Jahan Hridi; Md. Hasanuzzaman; Md. Shafiqul Islam Khan (Health Science Reports, 2025)
ABSTRACT Background and Aims The COVID‐19 pandemic has intensified pre‐existing mental health issues in Bangladesh, yet no study has specifically examined how factors related to COVID‐19 vaccination influence mental health within this context. This study aimed to examine the relationship between mental health symptoms, including depression, anxiety, and stress, and COVID‐19 vaccination status and related factors among the adult Bangladeshi population. Methods A cross‐sectional study with a convenience sampling technique was employed to gather the data. The sample size and response rate were 1085 and 93.68%. The mean age of the participants was 34.30 (SD: 12.79), and 55.3% were female. Descriptive and inferential statistics were carried out. Results The reliability of the instruments, measured by Cronbach's alpha, was: depression (0.78), anxiety (0.82), stress (0.83), and overall DASS (0.92). The average number of COVID‐19 vaccine doses taken was 2.33. Each additional dose of the COVID‐19 vaccine significantly reduces stress scores by 0.61. Additionally, pre‐vaccination concerns about side effects significantly increase anxiety scores by 0.63. Furthermore, experiencing pressure to get vaccinated is associated with a significant increase in depression scores by 0.78. Moreover, experiencing negative outcomes from the vaccine significantly decreases scores across all three mental health metrics: depression by −0.91, anxiety by −0.87, and stress by −1.35. Conclusion This study reveals the broad psychological consequences of COVID‐19 vaccination in Bangladesh, which underscore the importance of effective communication and supportive strategies, alongside targeted psychological interventions at vaccination sites.